Kajian Ekonomi Pengeluaran Pemerintah untuk Penanganan Covid-19 dan Dampaknya Terhadap Masyarakat di Kabupaten Ende - Kewa, Maria Mediatrix Tewele; Sagajoka, Estherlina; Sedho, Yuliana (JURNAL EQUILIBRIUM, 2022)
This study aims to determine the size of the budget issued by the Government of Ende Regency in the context of handling Covid-19 in Ende Regency, to determine the sectors that receive the Covid-19 budget in Ende Regency and to find out people's responses regarding the economic benefits and social benefits of the budget. Covid-19 in Ende Regency. The method used in this research is descriptive quantitative and qualitative using the analysis tool Benefit Cost Ratio. The results of this study indicate that: first, the amount of budget issued by the Government of Ende Regency in the context of handling Covid-19 in Ende Regency is IDR 55,228,588,228. The two sectors that received the Covid-19 budget were the Health sector 80% with a budget of IDR 44,201,033,800, the economic sector 13% with a budget of IDR 7,278,947,928 and the social safety network sector 7% with a budget of IDR 3,748,606,500. The three results of the Benefit Cost Analysis of government spending for the Covid-19 budget in Ende Regency are 0.9 If viewed from the aspect of investment feasibility, the government program for handling the impact of Covid-19 is not feasible because it has a BCR value <1, but after a review of the benefits aspect namely economic benefits and social benefits, the public opinion of 43 respondents is that with the existence of the Ende Regency government expenditure for handling the impact of the Covid-19 pandemic through assistance provided to the community, which is very beneficial for the people of Ende Regency and for social benefits from government programs carried out for humanity , this was done because to save the lives of many people.